Diagnostic utility of direct immunofluorescence findings around hair follicles and sweat glands in immunobullous disease. (1st November 2012) - Lehman, Julia S.; Camilleri, Michael J.
<x xml:space="preserve">Abstract</x> Background Inherent to some immunobullous disorders is potential for intraepidermal or dermal–epidermal junction fragility, a phenomenon that may compromise biopsy specimen integrity and direct immunofluorescence (DIF) interpretation. In these situations, cutaneous adnexal structures (e.g. hair follicles, sweat apparatus) usually remain intact. Whether periadnexal DIF findings are reliable in diagnosing immunobullous conditions is unknown. Methods We evaluated 56 cutaneous specimens with diagnostic immunoglobulin (Ig) deposition patterns that contained adnexal structures. In a corollary study, we examined 145 hematoxylin‐eosin‐stained frozen specimens to determine biopsy factors associated with the presence of adnexal structures. Results Periadnexal DIF findings offered diagnostic sensitivity in conditions with linear or cell‐surface Ig deposition or lupus band. Periadnexal DIF findings were unreliable in dermatitis herpetiformis. Biopsy specimens from scalp and genitalia were most likely to contain folliculosebaceous units and sweat duct apparatus, respectively. Relative depth of biopsy correlated directly with the likelihood of identifying sweat duct apparatus but not folliculosebaceous units. Conclusions Periadnexal DIF findings may add diagnostic sensitivity in DIF evaluation of pemphigoid, pemphigus and lupus erythematosus. Pathologists can guide clinicians to biopsy certain anatomic sites and to obtain sufficient biopsy depth to increase the probability of capturing adnexal structures and, therefore, diagnostic yield from DIF specimens.